Analysis of EFL students’ Errors in Writing at the Higher Teachers’ Training College of N’Djamena - Ngarsou, Voudina (English Studies at NBU, 2022)
This paper set to carry out an experimental study on ten students who were randomly selected and divided into two groups: control group (CG) and treatment group (TG). After being taught, the control group was asked to write a composition. The treatment group was also asked to write a composition on the same topic. This paper then compared their results. The findings in the study of the control group indicated that the most common errors committed by the learners were spelling errors which recorded the highest percentage with 24.24%, followed by word choice errors with 15.15%, and adjective related errors having 12.12%. Finally, this article indicates that the writing of learners of English as a foreign language was not free from errors even though they were appropriately taught.